Power Systems Simulation In Open Source Software - Gomez, Steven Jimenez; Varela, Sebastian Bustamante; Tabares, Brayan Arboleda (2024 IEEE URUCON, 2024)
The challenges posed by the analysis of modern power systems are increasingly demanding constant improvements in simulation times, implementation alternatives, and even the tools used. In accordance with these needs, it is pertinent to reevaluate traditional platforms. PowerFactory by DigSILENT has established itself as the software par excellence within the Colombian engineering context, being the widely used tool since the 1990s, representing a robust, powerful, and reliable tool. However, this type of platform is not without flaws, with limitations such as the cost of licenses, knowledge of low-level internal models, and updates conditioned by the manufacturer; key points that support the initiative to move the simulation environment towards an Open Source solution that allows the exploration of new practical horizons, enabling free and open access customization, knowledge of low-level functionality, and the possibility of widespread use. Bearing in mind the absence of intent to question the capabilities of PowerFactory, it becomes an exercise in exploration to test the capabilities of a python-based simulation environment, seeking new alternatives that expand, not replace, the range of possibilities for engineers, companies, etc. Thus, the python module, PyPSA, is proposed as the Open Source tool with which to validate the potential of this type of simulation and analysis solutions, using the Colombian National Interconnected System (SIN) database as a test subject, subjecting it to a migration, validation, and testing process under constraint and flexibility methodologies.